2001
DOI: 10.1046/j.1365-2842.2001.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral functional characteristics and gastrointestinal pathology: an epidemiological approach

Abstract: One of the main problems for aged people is that of having a balanced diet, improved by correct conditioning of the alimentary bolus. Does the masticatory status influence the appearance of gastrointestinal disorders? Such a question justifies the present study. The present work concerned all the patients (211) of eight geriatric institutions, and was completed by a retrospective approach (case-control study). The main result brought by the case-control study, showed that poor oral functional characteristics r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 6 publications
1
25
0
2
Order By: Relevance
“…Moreover, as the number of natural teeth increases, so does the chewing function perceived by the individual. Again in 2001, another study carried out by Tosello et al 28 stated that the risk of developing gastrointestinal pathologies was significantly higher among patients with chewing dysfunction than among those who had natural teeth. Researchers concluded that chewing dysfunction leads to consumption of semi-soft or soft foodstuffs or in other words low-fibre content food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as the number of natural teeth increases, so does the chewing function perceived by the individual. Again in 2001, another study carried out by Tosello et al 28 stated that the risk of developing gastrointestinal pathologies was significantly higher among patients with chewing dysfunction than among those who had natural teeth. Researchers concluded that chewing dysfunction leads to consumption of semi-soft or soft foodstuffs or in other words low-fibre content food.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most people lose height as vertebrae and discs compress with age. The internationally agreed threshold of acceptable BMI [20][21][22][23][24][25] , underweight (<20), overweight [25][26][27][28][29][30] , and obese (>30) was adopted. Data entry and all calculations were made with the software package SPSS version 15.0 for Windows (SPSS Inc., Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brodeur et al [12] and Tosello et al [88] repeatedly studied the correlation between edentulism and gastrointes- [53].…”
Section: Masticatory Function and Gastrointestinal Effectsmentioning
confidence: 99%
“…tinal diseases. In a Canadian study of seniors wearing dentures, 47% exhibited reduced masticatory efficiency [12,88]. These subjects were more apt to take medications for gastrointestinal disorders (such as antacids and antidiarrheal drugs) (37%) than those with better masticatory efficiency (20%).…”
Section: Kaufunktion Und Gastrointestinale Auswirkungenmentioning
confidence: 99%